(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
The paper deals with the explanatory value of speaking terms of emotion English and Mongolian cultures. While examining a number of emotion terms, the sources of confusion have been clarified and the real differences between English and Mongolian languages have been revealed. In applying the cross-cultural semantic theories, the cross-cultural comparison of emotions has been done. English terms of emotion constitute a folk taxonomy, not an objective, culture-free analytical framework while Mongolian terms of emotion are words that are derived from and related to the ways of Mongolian traditional nomadic civilization, religion, and customs. The main difference between Mongolian and English languages can be represented in terms of certain specifiable features, for instance, Mongolian emotion words, of course, are not all the same as the simple words that we use every day, but as mentioned above, it is important to study them on the basis of special distinctions of Mongolian language, Mongolian folk traditions, historical development of Mongolian language, Mongolian morphological system and sociolinguistics. In conclusion, different systems of emotion terms reflect different ways of conceptualizing emotions, and conversely, any cross-cultural similarities in the conceptualization of emotions will be reflected in the ways of different societies converge in the labelling of emotions. Монгол, англи соёл дахь сэтгэл хөдлөлийн нэр томьёоны утга Хураангуй: Энэхүү өгүүлэл нь монгол, англи соёлд хэрэглэж буй сэтгэл хөдлөлийн нэр томьёог утга зүйн талаас харьцуулан судалж, нийтлэг болон онцлог талыг тодруулахыг зорилоо. Судлаач Айзард, Бюехлер нарын боловсруулсан сэтгэл хөдлөлийн 10 нэр томьёо, Баянцагааны орчуулсан Бодь мөрийн зэрэг зохиолд тодорхойлсон монгол нэр томьёог судалгааны хэрэглэгдэхүүн болгон ашигласан болно. Соёл хоорондын утга судлалын судалгааны аргыг ашиглан харьцуулалт хийж, ойлгоход бэрхшээлтэй үгсийн утгын дэлгэрэнгүй тайлбарыг өгөв. Сэтгэл хөдлөлийн нэр томьёог соёл-хоорондын утга судлалын үүднээс задлан шинжлэхдээ хэл, соёлын онцлог, шинжлэх ухаанд хэрэглэгдэж буй байдал, хүний талаарх түгээмэл ойлголт зэргийг харгалзан үзэж, утгын тайлбар өгөх шаардлагатай болохыг судалгааны үр дүн харуулав. Харьцуулсан судалгаанаас харахад монгол хэлэнд хэрэглэгдэж буй сэтгэл хөдлөлийн нэр томьёо нь өдөр тутамд ашиглаж буй түгээмэл үг хэллэгээс утга, үүрэг, хэрэглээгээрээ өө байсан. Цаашид монгол соёлд хэрэглэж буй сэтгэл хөдлөлийн нэр томьёог монгол хэлний өвөрмөц онцлог, түүхэн хөгжил, үг зүйн тогтолцоо, ардын уламжлалыг үндэслэн, нийгэм хэл шинжлэлийн үүднээс нарийвчлан судлах шаардлагатай хэмээн үзэж байна. Түлхүүр үг: Сэтгэл хөдлөл, соёл хоорондын утга судлал, үг зүйн тогтолцоо Түлхүүр үг: Сэтгэл хөдлөл, соёл хоорондын утга судлал, үг зүйн тогтолцоо